PENINGKATKAN KEMAMPUAN SISWA MEMAHAMI POKOK BERITA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK DI KELAS X SMA NEGERI I RANTAU SELATAN TAHUN PEMBELAJARAN 2020 - 2021 - ANNIM HASIBUAN (JURNAL ILMIAH SIMANTEK, 2021)
The problem in this study is that the ability to understand student news is still low. To overcome this, a learning model isneeded that can improve students' ability to understand the subject, the learning model in question is the talking sticklearning model. The purpose of this study is to find out whether talking stick-type cooperative learning models can improvethe ability to understand the subject matter. This research is a PTK (Class Action Research) study by giving treatment to thegroup conducted using the talking stick learning model. The population of this study was all 40 high school students, whilethe sample of this study was as many as 40 students. The instruments used to capture the study data are observations andtests. Based on the results of the research obtained, it was concluded that the application of talking stick learning models canimprove students' ability to understand the subject matter, this is seen based on test results. In the pre-cycle, students whocompleted by 45%, when compared to the criteria of the level of completion of learning are at the criteria less once. Then incycle I increases to 70%, when compared to the completion criteria then it is on the criteria enough. In cycle II completionincreased back to 90%, when compared to the criteria of learning completion level is at very good criteria.